Adaptive control of uncertain non-linear fractional-order systems in the presence of actuator failures and input constraints - Masood Bagherzadeh (تصمیم گیری و تحقیق در عملیات)
Purpose: This paper studies the problem of adaptive actuator failure compensation in non-linear fractional-order systems with strict feedback forms and provides a theoretical framework for designing control systems in the presence of parametric uncertainties, input constraints, and actuator failures to ensure stability and output tracking.Methodology: An adaptive controller is designed to compensate for actuator failures and control input constraints. By correcting parametric, structural, and environmental uncertainties, the controller ensures the asymptotic stability of the closed-loop system and output tracking. Stability analysis is conducted using the Mittag-Lefler stability theorem, and numerical simulations are performed to validate the proposed method.Findings: The simulation results demonstrate the effectiveness of the proposed method in compensating actuator failures and input constraints while achieving closed-loop system stability and output tracking.Originality/Value: This research offers an innovative contribution to the field of control systems by employing adaptive control for actuator failure compensation in non-linear fractional-order systems and presenting a comprehensive theoretical framework, addressing both practical and theoretical challenges.